2018
DOI: 10.1080/08959285.2018.1539856
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a HEXACO situational judgment test

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 76 publications
(115 reference statements)
1
48
1
3
Order By: Relevance
“…Thus, SMEs with job experience in the domain in question are typically relied on to form SJT scoring keys (Motowidlo et al, 1990). However, SJTs are also used to measure more generalizable individual differences such as emotional intelligence (MacCann & Roberts, 2008) and personality (Oostrom, de Vries, & de Wit, 2019). Thus, depending on the extent to which an SJT measures job-specific knowledge versus more generalizable individual difference constructs, SME-derived scoring keys may be comparable to those produced by large groups of novices.…”
mentioning
confidence: 99%
“…Thus, SMEs with job experience in the domain in question are typically relied on to form SJT scoring keys (Motowidlo et al, 1990). However, SJTs are also used to measure more generalizable individual differences such as emotional intelligence (MacCann & Roberts, 2008) and personality (Oostrom, de Vries, & de Wit, 2019). Thus, depending on the extent to which an SJT measures job-specific knowledge versus more generalizable individual difference constructs, SME-derived scoring keys may be comparable to those produced by large groups of novices.…”
mentioning
confidence: 99%
“…Note that only the Emotional stability and the Conscientiousness scales showed alpha coefficients below .70. The alpha coefficients of these two scales are similar to or even higher than the alpha coefficients of other personality scales with a similar number of items per scale, including the brief version of the HEXACO‐PI‐R (BHI; De Vries, ) and the HEXACO‐SJT (Oostrom et al, ).…”
Section: Methodsmentioning
confidence: 62%
“…However, as time is often a limited resource and long measures increase the likelihood of fatigue, boredom, and burden among participants (Romero, Villar, Gómez‐Fraguela, & Lopez‐Romero, ), interest in developing short measures has grown considerably (Credé, Harms, Niehorster, & Gaye‐Valentine, ). Importantly, there is more and more evidence showing that the effects on validity of short personality measures with generally low alpha coefficients are not as large as previously feared (De Vries, ; Gosling, Rentfrow, & Swann, ; Oostrom, De Vries, & De Wit, ; Romero et al, ). Therefore, we believe future PO fit studies might profit most from a short commensurate personality measure.…”
Section: Introductionmentioning
confidence: 94%
“…Samples for the SJT items and BDI questions are shown in Table 2. Past studies on personality-based SJTs have reported internal consistencies between α = 0.55 and α = 0.75 (Mussel et al, 2018), and between α = 0.22 and α = 0.66 (Oostrom et al, 2019). Past studies on personality-based BDIs reported ICCs (interrater reliability) of 0.78 (Heimann et al, 2020) and 0.74 (Van Iddekinge et al, 2005).…”
Section: Sample Questionmentioning
confidence: 99%
“…To date, few studies have developed personality SJTs or BDIs and even fewer have measured established personality traits such as the Big Five (Goldberg, 1992 ). The few studies that exist, however, suggest that SJTs and BDIs might be useful for measuring personality (Van Iddekinge et al, 2005 ; Oostrom et al, 2019 ; Heimann et al, 2020 ). Accordingly, more research on complementary measurements of personality is needed to foster this initial evidence and to systematically compare these new measures with each other.…”
Section: Introductionmentioning
confidence: 99%